Melatonin level and sleep disorders in adolescents - Andre Inigo; Hesti Lestari; Nurhayati Masloman; Julius Lolombulan (Paediatrica Indonesiana, 2015)
Background Sleep disorder is defined as a disturbance in the quality and time of sleep. Decreased melatonin levels have been noted in people with sleep disorders. Melatonin is a neurohormone, produced mainly by the pineal gland, as well as a small part of the retina. Its function is to maintain normal circadian rhythms and it is related to sleep regulation in humans.Objective To assess for a relationship between melatonin levels and sleep disorders in adolescents.Methods We conducted a cross-sectional study on students of two secondary schools in Tuminting, Manado, North Sulawesi, from May to June 2013. Subjects were obtained by consecutive sampling for a total of 44 adolescents aged 12-15 years. Subjects filled questionnaires, underwent wrist actigraphy, and provided blood specimens for examination of melatonin levels. We used descriptive and logistic regression analyses to assess for relationships between variables.Results Thirty (68.2%) subjects experienced sleep disorders. There was a significant association between decreased melatonin levels and the higher incidence of sleep disturbances (P = 0.02).Conclusion There is a correlation between melatonin levels in adolescents with sleep disorders. Decreased melatonin levels are associated with sleep disorders.